The impact of aircraft capacity utilization on bankruptcy probability before and during Covid-19: Evidence from publicly-listed airlines in Asia, Europe, and the Americas from 2002 to 2021 - Huang, Trisha T. (Animo Repository, 2023)
Over the years, financial stability has remained a pressing issue for the aviation industry because of cutthroat competition, high fixed costs, and unstable demand for air transport. Airline companies around the world are particularly susceptible to financial distress during socio-economic shocks which significantly reduce the demand for air travel such as the 9/11 attacks. The recent Covid-19 pandemic has had a devastating impact on airlines, with several large carriers worldwide filing for bankruptcy. A key element of airline profitability is their ability to maximize their capacity utilization, which allows them to generate revenues that are more than sufficient to cover their high fixed costs. Due to the global economic condition, revisiting the impact of aircraft capacity utilization on the bankruptcy probability of airlines would be timely. The latest studies were conducted primarily for companies in a single location and failed to include data relating to airline companies during Covid-19. Hence, we sought to assess the impact of aircraft capacity utilization on bankruptcy probability of publicly-listed airline companies in Asia, Europe, and the Americas from 2002 to 2021 using data from Refinitiv Eikon. Controlling for both firm attributes (firm age and firm size) and external factors (GDP growth rate and jet fuel prices), we found that aircraft capacity utilization does not significantly impact the bankruptcy probability of airlines overall. However, we found evidence among European airlines that higher aircraft capacity utilization leads to higher bankruptcy probability.